Influence of the School Orientation of the High School Students on Their School Career - N.Chiboub; M.Tridane; S.Belaaouad (Iraqi Journal of Science, 2021)
The orientation allows the individual to develop the capacity to become aware of his personal characteristics and to develop them in order to choose his studies, his training and his professional activities, in all the conjunctures of his existence, with the joint concern for the collective future of solidarity and the fulfillment of one's personality and responsibilityÂ». (Danvers, 1992,p. 190). This advice states that: orientation is a process closely associated with education and formation. It becomes effective if the steps include broad information on education and trades, and focuses on the social development and moral construction of the individual. The objective of this survey is to show the influence of the orientation of the pupils at the time of their passage from the midl school to the high school on their school course. It aims to find the causes of their misdirection to minimize its negative impact on their academic performance, on the choice of their higher education and subsequently on their future. Our research is based on an analysis of the results of a questionnaire intended for students of the common core (first year of high school) of the scientific, literary and technical, public institutions of the secondary school located in the region of Casablanca - Settat( Morocco), exactly in the regional direction of MoulayRachid-Sidi Othman, during the school year 2016/2017. It was preceded by a series of interviews with students, teachers, guidance counselors, and the director of the provincial center for information and help to orientation as well as with other stakeholders in the field of the education for the calibration of the vocabulary and Themes landed. Our survey allowed us to discover very important results on the influence of the orientation of the pupils on their school course that we are going to present and to discuss.